2018
DOI: 10.1371/journal.pone.0196050
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition effect of pyridoxamine on lipid hydroperoxide-derived modifications to human serum albumin

Abstract: Pyridoxamine (PM) is a promising drug candidate for treating various chronic conditions/diseases in which oxidative stress and carbonyl compounds are important factors affecting pathogenicity. These abilities of PM are mainly attributed to its inhibition of advanced glycation and lipoxidation end product formation, by scavenging reactive carbonyl species. PM might therefore prevent protein damage from lipid hydroperoxide-derived aldehydes such as 4-oxo-2(E)-nonenal (ONE) and 4-hydroxy-2(E)-nonenal (HNE) by tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…PM acts also by directly trapping MDA modified serum albumin, thus under physiological conditions reducing generation of lipofuscin-like fluorescence [112]. In addition, modification of lysine residues on serum albumin by 4-oxo-nonenal can be decreased after treatment with PM [113], but it is not effective in case of albumin modification by 4-HNE, which is mostly binding to the histidine residues of the albumin.…”
Section: Redox Signaling Pathways Involving 4-hne In Cardiovascular Disorders and Related Therapiesmentioning
confidence: 99%
“…PM acts also by directly trapping MDA modified serum albumin, thus under physiological conditions reducing generation of lipofuscin-like fluorescence [112]. In addition, modification of lysine residues on serum albumin by 4-oxo-nonenal can be decreased after treatment with PM [113], but it is not effective in case of albumin modification by 4-HNE, which is mostly binding to the histidine residues of the albumin.…”
Section: Redox Signaling Pathways Involving 4-hne In Cardiovascular Disorders and Related Therapiesmentioning
confidence: 99%
“…The combination of the two conjugated functional groups of 4-HNE, the carbonyl group (-C =0), and a double bond (C2/C3, -C=C-) facilitates the reaction of 4-HNE with biological molecules (including lipids, nucleic acids, and proteins) [ 39 ]. A mass spectrometry-based proteomic analysis of oxidative stress found that the electrophilic double bond and nucleophilic amino acid residues on proteins enable 4-HNE to form Michael adducts with lysine (Lys) [ 40 ], histidine (His) [ 41 ], and cysteine (Cys) [ 42 ] residues to increase the molecular masses of these amino acids by 156 Da (the molecular mass of HNE), or form Schiff-base adducts with its aldehyde group and Lys to an increase in the mass by 138 Da (Schiff-base formation with a net loss of water) [ 43 , 44 ]. Moreover, the research of proteomic analysis of in vitro histone carbonylation sites showed that Schiff-base modification is labile and reversible, while that of Michael adducts are stable and non-reversible [ 45 ].…”
Section: 4-hydroxy-2-nonenalmentioning
confidence: 99%
“…Interestingly, the molecule has multiple beneficial effects that are carried out by two functional groups, the hydroxyl and the aminomethyl group [ 135 ]. Among the effects is the inhibition of AGEs and ALEs formation by scavenging reactive carbonyl species [ 134 , 136 , 137 ], the sequestration of catalytic metal ions [ 138 ], the blockage of oxidative degradation of Amadori intermediates derived from glycated proteins [ 139 ], ROS and free radicals scavenging [ 140 ].…”
Section: Clinical and Pre-clinical Drugs With Aldehyde Scavenging Pro...mentioning
confidence: 99%